La scène de la page - Ligia Souza (Appareil)
This study aims to promote a reflection on select theatrical editions in relation to the creation of artist books, through an analysis of French Fries by Dennis Bernstein and Warren Lehrer. Stimulating a theoretical debate between artists and researchers in visual and performance arts, the article introduces the concept of Portable Theater to connect the materiality of books with theatrical materiality. It also addresses topics such as paraspectacularity, theatrical presence, mental theater, and the imaginary museum. Finally, the study emphasizes a collection of Brazilian works that emphasize the material construction of theater editions, understood as Portable Theater, a source of potential cross-temporal-liveness.